2018
DOI: 10.3389/fphys.2018.01806
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Electrophysiological Effects of Light-Activated Chloride Channels

Abstract: During the last decade, optogenetics has emerged as a paradigm-shifting technique to monitor and steer the behavior of specific cell types in excitable tissues, including the heart. Activation of cation-conducting channelrhodopsins (ChR) leads to membrane depolarization, allowing one to effectively trigger action potentials (AP) in cardiomyocytes. In contrast, the quest for optogenetic tools for hyperpolarization-induced inhibition of AP generation has remained challenging. The green-light activated ChR from G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…ArchT-mediated cardiomyocyte hyperpolarization has also been used to terminate ventricular arrhythmias in the intact hearts of transgenic mice (Funken et al, 2019). As expected from the chloride reversal potential in cardiomyocytes, recent work (Kopton et al, 2017, 2018) has highlighted that cardiomyocytes in culture demonstrate excitation in response to light stimulation with both naturally occurring and engineered chloride channels. This can be explained by the fact that the reversal potential for chloride in the cardiomyocyte is more positive than the resting membrane potential, thus optically opening chloride channels tends to lead to membrane depolarization (Hiraoka, 1998).…”
Section: Selecting An Opsin For Cardiac Optogenetics: Directionalitymentioning
confidence: 91%
See 1 more Smart Citation
“…ArchT-mediated cardiomyocyte hyperpolarization has also been used to terminate ventricular arrhythmias in the intact hearts of transgenic mice (Funken et al, 2019). As expected from the chloride reversal potential in cardiomyocytes, recent work (Kopton et al, 2017, 2018) has highlighted that cardiomyocytes in culture demonstrate excitation in response to light stimulation with both naturally occurring and engineered chloride channels. This can be explained by the fact that the reversal potential for chloride in the cardiomyocyte is more positive than the resting membrane potential, thus optically opening chloride channels tends to lead to membrane depolarization (Hiraoka, 1998).…”
Section: Selecting An Opsin For Cardiac Optogenetics: Directionalitymentioning
confidence: 91%
“…This can be explained by the fact that the reversal potential for chloride in the cardiomyocyte is more positive than the resting membrane potential, thus optically opening chloride channels tends to lead to membrane depolarization (Hiraoka, 1998). This property has been flexibly used in experimental preparations to allow either optical pacing of cardiac contractions in response to short pulses of light, or silencing of cardiomyocyte activity with prolonged activation through the induction of depolarization block (Kopton et al, 2018). Interestingly, other studies demonstrated an opposite effect on membrane potential, with ACRs eliciting large hyperpolarizing photocurrents with intracellular Cl − concentrations adjusted by the patch pipette to 4 mM (Govorunova et al, 2016).…”
Section: Selecting An Opsin For Cardiac Optogenetics: Directionalitymentioning
confidence: 99%
“…In fact, in cardiomyocytes, light-induced activation of anion-conducting channels at resting membrane potential leads to depolarization as shown elegantly by Kopton et al. in this Research Topic article collection (Kopton et al., 2018). Recently, K + selective light-gated ion channels have been described for optogenetic silencing of electrical activity but with very slow off kinetics (Alberio et al., 2018; Bernal Sierra et al., 2018).…”
Section: Introductionmentioning
confidence: 90%
“…Importantly being an unidirectional outward pump, ArchT induces hyperpolarization without a reversal potential, which is an advantage over optogenetic Cl − or K + conducting ion channels, which are ineffective or even depolarizing at membrane potentials close or below their reversal potential, respectively (Govorunova et al, 2015; Alberio et al, 2018; Bernal Sierra et al, 2018). Specifically, the recently identified Cl − selective channelrhodopsin variants are not suited because the high intracellular Cl − concentration results in light-induced depolarization in cardiomyocytes as elegantly described by Kopton et al (2018) in this focused issue. Importantly, optogenetic hyperpolarization of cardiomyocytes has been used before in vitro by co-culture with ArchT-expressing fibroblasts (Nussinovitch et al, 2014) and in ArchT-expressing human induced pluripotent stem cell-derived cardiomyocytes (Quach et al, 2018).…”
Section: Introductionmentioning
confidence: 99%